Exploring pitch and length perception: An EEG study on quantity discrimination in preschoolers with developmental language disorder - Liis Themas; Erik Samuel Nickel; Pärtel Lippus; Marika Padrik; Kairi Kreegipuu (Acta Psychologica)
Objective: This study investigates the perception of pitch and duration – the main features of the Estonian three-way quantity distinction – in children with developmental language disorder (DLD). Method: We used EEG and behavioral tasks to measure quantity perception in 50 children, half with DLD with mean age of 69 months (±6 months; 26 males). We employed cluster-based permutation tests to examine ERPs and time-frequency representations and linear mixed models (LMM) to explore the influence of participant-related factors on the neurophysiological measures. Results: The LMM indicated that the DLD group showed a more positive mismatch response (MMR) than controls in the duration change condition. The model estimated that in the DLD group, MMR amplitude became increasingly negative with age, whereas it became increasingly positive in controls. No group differences were observed in Late Discriminative negativity or P1. No differences were found between the time-frequency representations of the standard and deviant conditions, and no discrimination was detected in the pitch plus duration change condition. Conclusion: Children with DLD exhibit distinct MMR to duration change. Significance: This research offers valuable insights into the developmental trajectory of the MMR, suggesting that it may not be a straightforward progression from positive to negative. Further, it advances both clinical understanding and cross-linguistic research in developmental language disorder.